Designing tough isotropic structural composite using computation, 3D printing and testing. (15th June 2019) - Kim, Yongtae; Kim, Youngsoo; Libonati, Flavia; Ryu, Seunghwa
Abstract: Staggered platelet composites found in nature, such as nacre, bone, and conch-shell, exhibit a remarkable combination of high toughness, strength, and/or stiffness, and have inspired the development of bio-inspired composites mimicking their characteristic features. However, those excellent mechanical properties are primarily observed under specific loading conditions due to their mechanical anisotropy, which originates from the aligned microstructures consisting of high aspect ratio inclusions. In this study, we combine numerical simulations and 3D-printing to define a design strategy of isotropic two-dimensional structural composites consisting of stiff and soft constituents that are arranged in square, triangular, and quasicrystal lattices. For relatively isotropic structures, the soft tile/stiff boundary configuration significantly outperforms the stiff tile/soft boundary configuration in terms of normalized toughness, strength, and stiffness with respect to the simple rule of mixture estimates for each, because the former provides more extrinsic toughening mechanisms and effectively lowers the stress concentration near the crack tip. The quasicrystal lattice offers the best isotropy in elastic response, while its absolute values of stiffness, strength, and toughness turn out to be similar or lower than those of triangular lattice composites due to more irregular stress distribution. In contrast, for the highly anisotropic staggered platelet structure, the stiff tile/soft boundary configuration significantly outperforms the inverted one, owing to its unique load-transfer mechanism, which relies primarily on the shear-lag effect. Graphical abstract: Image 1